Molecular characterization of a fungal gene paralogue of the penicillin penDE gene of Penicillium chrysogenum - García-Estrada, Carlos; Vaca, Inmaculada; Ullán, Ricardo V; van den Berg, Marco A; Bovenberg, Roel AL; Martín, Juan Francisco (BMC microbiology, 2009)
Penicillium chrysogenum converts isopenicillin N (IPN) into hydrophobic penicillins by means of the peroxisomal IPN acyltransferase (IAT), which is encoded by the penDE gene. In silico analysis of the P. chrysogenum genome revealed the presence of a gene, Pc13g09140, initially described as paralogue of the IAT-encoding penDE gene. We have termed this gene ial because it encodes a protein with high similarity to IAT (IAL for IAT-Like). We have conducted an investigation to characterize the ial gene and to determine the role of the IAL protein in the penicillin biosynthetic pathway. The IAL contains motifs characteristic of the IAT such as the processing site, but lacks the peroxisomal targeting sequence ARL. Null ial mutants and overexpressing strains indicated that IAL lacks acyltransferase (penicillin biosynthetic) and amidohydrolase (6-APA forming) activities in vivo. When the canonical ARL motif (leading to peroxisomal targeting) was added to the C-terminus of the IAL protein (IAL ARL) by site-directed mutagenesis, no penicillin biosynthetic activity was detected. Since the IAT is only active after an accurate self-processing of the preprotein into alpha and beta subunits, self-processing of the IAL was tested in Escherichia coli. Overexpression experiments and SDS-PAGE analysis revealed that IAL is also self-processed in two subunits, but despite the correct processing, the enzyme remained inactive in vitro. No activity related to the penicillin biosynthesis was detected for the IAL. Sequence comparison among the P. chrysogenum IAL, the A. nidulans IAL homologue and the IAT, revealed that the lack of enzyme activity seems to be due to an alteration of the essential Ser309 in the thioesterase active site. Homologues of the ial gene have been found in many other ascomycetes, including non-penicillin producers. Our data suggest that like in A. nidulans, the ial and penDE genes might have been formed from a single ancestral gene that became duplicated during evolution, although a separate evolutive origin for the ial and penDE genes, is also discussed.